PERFORMANCE OF FISHERIES BUSINESS GROUP (KELOMPOK USAHA BERSAMA) IN BULUH ISLAND BULANG DISTRICT BATAM CITY PROVINCE OF RIAU ISLANDS - Ade Fahrizal; Darwis Darwis; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in April 2018 in Buluh Island, Bulang District, Batam City, Riau Islands Province. This study aims to determine the profile and activeness of KUB on Buluh Island. In addition, this study also aims to determine the performance of the Joint Business Group (Kelompok Usaha Bersama) by looking at several aspects, namely the Institutional Aspects, Economic Aspects and Environmental Aspects of Buluh Island. With 34 respondents, namely the chairman, secretary and group members.The results of this study indicate that all Joint Business Groups are always actively participating in carrying out the big day activities in Buluh Island by distributing KUB members to take part in the implementation of activities in Buluh Island, one of the activities carried out in Buluh Island is compensation orphans, Republic of Indonesia Anniversary, religious activities (such as Isra Mi'raj celebrations), coastal reforestation and participating in trainings held by extension workers (such as BIMTEK). In general, the performance of the Joint Business Group (Kelompok Usaha Bersama) can be categorized both at the level of KUB members and the community and can be seen from community participation so that the institutionalization of the Joint Business Group (Kelompok Usaha Bersama) activities in Buluh Island, Bulang District, Batam Island Province. Keywords: Performance, Joint Business Group (Kelompok Usaha Bersama), Fisherman Community.